Heritage and the existential need for history - Webster, Maud (Florida scholarship online, 2021)
In a sweeping survey of archaeological sites spanning thousands of years, this book asks fundamental questions about the place of cultural heritage in Western society. What is history? Why do we write about the events of yesterday and set up memorials for them? Why do we visit places where momentous things have happened?